HSV-1 latent rabbits shed viral DNA into their saliva - Hill, James M (BioMed Central, 2012)
BACKGROUND: Rabbits latent with HSV-1 strain McKrae spontaneously shed infectious virus and viral DNA into their tears and develop recurrent herpetic-specific corneal lesions. The rabbit eye model has been used for many years to assess acute ocular infections and pathogenesis, antiviral efficacy, as well as latency, reactivation, and recurrent eye diseases. This study used real-time PCR to quantify HSV-1 DNA in the saliva and tears of rabbits latent with HSV-1 McKrae. METHODS: New Zealand white rabbits used were latent with HSV-1 strain McKrae and had no ocular or oral pathology. Scarified corneas were topically inoculated with HSV-1. Eye swabs and saliva were taken from post inoculation (PI) days 28 through 49 (22 consecutive days). Saliva samples were taken four times each day from each rabbit and the DNA extracted was pooled for each rabbit for each day; one swab was taken daily from each eye and DNA extracted. Real-time PCR was done on the purified DNA samples for quantification of HSV-1 DNA copy numbers. Data are presented as copy numbers for each individual sample, plus all the copy numbers designated as positive, for comparison between left eye (OS), right eye (OD), and saliva. RESULTS: The saliva and tears were taken from 9 rabbits and from 18 eyes and all tested positive at least once. Saliva was positive for HSV-1 DNA at 43.4% (86/198) and tears were positive at 28.0% (111/396). The saliva positives had 48 episodes and the tears had 75 episodes. The mean copy numbers ± the SEM for HSV-1 DNA in saliva were 3773 ± 2019 and 2294 ± 869 for tears (no statistical difference). CONCLUSION: Rabbits latent with strain McKrae shed HSV-1 DNA into their saliva and tears. HSV-1 DNA shedding into the saliva was similar to humans. This is the first evidence that documents HSV-1 DNA in the saliva of latent rabbits.